Numerical simulation of vegetated flows using RANS equations coupled with a porous media approach in OpenFOAM - Soares, António José Espadinha Vieira (2017)
The purpose of this Masters thesis is to study the use of an alternative formulation of a submerged vegetation layer in open channel flow, using a porous medium instead. The turbulent flow is modelled with the use of Reynolds-Averaged Navier-Stokes (RANS) equations using the open-source toolbox Open source Field Operation And Manipulation (OpenFOAM). The porous medium is defined according to the Darcy-Forchheimer model which requires the determination of the intrinsic permeability and passability coefficients. These parameters are estimated from the average geometric properties of the vegetation elements in a method validated in previously published studies. This method elimi- nates the ad hoc calibration required in the use of global drag coefficients in the RANS equations traditionally used to take into account the effects of submerged vegetation on open-channel flow. The use of this methodology has been previously partially validated using commercial numeric simulation codes. However, these tend to be costly solutions and very limited in their customizability. This study seeks to partially reproduce work done on the commercial code ANSYS-CFX in an open-source code environment as well as to try and conduct numeric studies of other open-channel flow experiments with a range of varied submerged vegetation parameters (ergo, porosity values) so as to not only test the robustness of the numeric code but of this methodology as well. This work’s methodology also took on a more simplified numerical solution approach by use of a less robust algorithm (with no time derivative) than previously conducted studies. It was then possible to further understand the types of phenomena present in this type of flow and the required theoretical considerations which should be taken into account so as to produce valid computational study results.